Trade liberalisation and child welfare - Escobal, J; Ponce, C (2007)
Peru is in the process of negotiating a free trade agreement (FTA) with the USA which would eliminate trade concessions on most goods and services. This paper analyses the potential impacts of such extensive trade liberalisation for Peru. The focus is on possible short-term welfare impacts and especially on child related welfare outcomes. The effects of a full and abrupt elimination of tariffs as part of a FTA are estimated in a general equilibrium framework - a branch of theoretical microeconomics which seeks to explain production, consumption and prices in a whole economy. Using this framework the connection between domestic prices and household welfare are modelled. Additionally, the demographic profiles of the most vulnerable population groups are analysed to assess whether children will be at an increased risk. The modelling exercise identifies potential negative short-term impacts of a FTA particularly for households in rural areas. Based on these findings the authors suggest a gradual reduction of tariffs to allow time for policies to be developed to boost rural productivity and the ability to withstand external competition. The authors conclude that a FTA could have different negative short-term effects on children’s welfare, such as increased child labour and school drop-out rates. Therefore they recommend the creation and strengthening of social safety nets and welfare programmes as a measurement to protect children from negative effects of a FTA with the USA.